The RESEARCH MAPPING: THE MILLENNIAL GENERATION AND CONSUMPTION OF FAKE PRODUCTS - Edy Purwo Saputro, Edy; Irawati, Zulfa; Setyaningrum, Dewi Probowati (LPPM STIE EKA PRASETYA, 2024)
Counterfeit products are not only a serious threat to the sustainability of the production process but also have a systemic impact on the economy and business economy. Therefore, the consumption of counterfeit products is a threat to marketing and on the other hand can damage the perception of the market leader. Therefore, research related to the consumption of counterfeit products in the current era is important. The long-term goal of this research is to build collective awareness to consume original products. The mapping results explain that there are various factors that influence behavior towards the consumption of counterfeit products, not only in Asia but also in Europe. Research findings show that there is a challenge to reduce the circulation of counterfeit products. Limitations and suggestions for further research are presented so that they can provide an overview of theoretical depth